Planning and evaluating academic resources - Baume, David, 1943- (The University of Hull)
One of a series of guides on the evaluation of academic practice, academic development units, resources, events, activities and services. This guide, like the others in this series, is modified from an evaluation framework produced for the six Higher Education Academy Science, Technology, Engineering and Maths (STEM) Subject Centres in 2009. These Subject Centres consist of Biosciences, Engineering, Information and Computer Science, Materials Science, Maths Stats and OR and Physical Sciences. The author, Dr David Baume, adbaume@aol.com, is happy to be contacted for advice and support on using this evaluation tool and others in the series.